Die kardiale Amyloidose – ein Krankheitsbild im Wandel - Mahrholdt, Heiko; Klingel, Karin; Sechtem, Udo (DMW - Deutsche Medizinische Wochenschrift, 2018)
A fast and reliable diagnosis of cardiac amyloidosis requires a significant amount of clinical awareness. It is especially important to come to an early diagnosis in patients with cardiac AL amyloidosis in order to improve the otherwise unfavourable clinical course in these patients. There is a significant increase in the number of patients with cardiac amyloidosis of the ATTR wild-type variety. These patients are often elderly males presenting with predominantly right sided heart failure. We present a diagnostic pathway enabling a structured approach to these patients using multimodality cardiac imaging and endomyocardial biopsy. Early chemotherapy is the key to improving symptoms in patients with AL amyloidosis. In contrast, pharmacologic approaches for treating cardiac ATTR amyloidosis need further research and clinical trials.
Keywords: kardiale Amyloidose; kardiale Magnetresonanztomografie; Knochenszintigrafie; Endomyokardbiopsie; neue Therapieansätze